Synthesis and spectroscopic properties of a prototype single molecule dual imaging agent comprising a heterobimetallic rhenium-gadolinium complex. - Koullourou, T; Natrajan, L; Bhavsar, H; Pope, S; Feng, J; Narvainen, J; Shaw, R; Scales, E; Kauppinen, R; Kenwright, A; Faulkner, S (2008)
A luminescent d-f hybrid containing a [Re(bpy)(Ar)(CO)3]+ chromophore and a gadolinium ion bound in a DO3A-derived binding pocket has been prepared. This complex combines long-lived luminescence from the 3MLCT state of the transition metal chromophore with high relaxivity, making it suitable for MRI imaging and luminescence imaging. The analogous complex containing ytterbium exhibits sensitized emission from both the ytterbium center and long-lived emission from the 3MLCT state. Copyright © 2008 American Chemical Society.